Psycho-Social Disorders Due To Verbal Bullying At The State Junior High School No. 4 Tenggarong - Wiwik Angranti (International Journal of Global Community, 2019)
Verbal bullying is very difficult to know the signs because there are no physical signs visible. But verbal bullying is more about the psychological side that the victim will remember for the rest of his life. Verbal bullying can also be done secretly, especially in the current social media era, someone can bully others anonymously, so the term cyber bullying now appears. The cause of verbal bullying occurs because of the weak role of parents in the family, the characteristics of students or negative actors, and the opportunity. The impact of verbal bullying experienced by victims is students experiencing psycho-social disorders. As students withdraw from their surroundings, crises of self-confidence, stress, anger, and depression. In addition to the impacts that occur on the victims there are also impacts experienced by the perpetrators. The perpetrators of verbal bullying usually have very high self-esteem, are irritable, and aggressive.